Characterisation of precipitates formed in 26% Cr super ferritic stainless steel. (25th November 2016) - Ma, L.; Hu, S. S.; Shen, J. Q.
Abstract : In this study, a newly designed super ferritic stainless steel, 26Cr–4Mo–2Ni, was developed and heated to 800°C for different durations to study the precipitation behaviour of various intermetallic phases, which determined its final mechanical and corrosion resistance properties. The types, numbers and distribution of typical precipitates were investigated. Besides TiN and Nb(C, N), which are common phases formed in Ti- and Nb-stabilised ferritic stainless steel, the Laves, chi ( χ ) and sigma ( σ ) phases were also detected in the grain boundary and grain interiors, depending on the aging times . The study focused on the morphology and regularity of these intermetallic precipitates. And the effect of precipitation on the mechanical properties and the corrosion resistance were discussed.